Surgical Outcomes of Transperitoneal Para-Aortic Lymphadenectomy Compared With Extraperitoneal Approach in Gynecologic Cancers: A Systematic Review and Meta-Analysis - Li, Kun-peng; Deng, Xian-zhong; Wu, Tao (Frontiers in Surgery, 2021)
Purpose: The optimal surgical approach for para-aortic lymphadenectomy (PALND) in gynecologic cancers using minimally invasive surgery (laparoscopy or robotic-assisted) is controversial. This study summarizes the current evidence on extraperitoneal (EP) approach and compares its perioperative, surgical outcomes, and complications to transperitoneal (TP) approach in an updated meta-analysis. Methods: We performed a systematic search in Pubmed, Embase, Web of Science, Cochrane Library database for RCTs and non-RCTs that compare EP to TP for PALND. The main outcomes included surgical, perioperative outcomes and complications. The weighted mean difference (WMD) and odds ratio (OR) were applied for the comparison of continuous and dichotomous variables with 95 per cent confidence intervals. Three RCTs and ten non-RCTs trials, including 2354 patients were identified and enrolled in the meta-analysis. Results: Three RCTs and ten non-RCTs trials, including 2354 patients were identified and enrolled in the meta-analysis. We reported similar results for EP and TP in terms of the hospital stay, estimated blood loss, blood transfusion, conversion to laparotomy, total operative time and postoperative complications (Clavien grade ≥1 and Clavien grade ≥3). However, the PALND operative time (WMD -10.46 mins, 95% CI -19.04, -1.88; p = 0.02) and intraoperative complications (OR 0.40, 95% CI 0.23, 0.69; P=0.001) were less with EP. Also, more nodes were removed in EP compared with the TP (WMD 1.45, 95% CI 0.05, 2.86; p = 0.04). Conclusions: The EP approach did not show differences regarding surgical and perioperative parameters compared with the TP approach. However, the number of aortic nodes retrieved was higher. Furthermore, The PALND operative time and intraoperative complications were less in EP.